Citizenship policies in the Baltic states and Ukraine - Petrauskas, Zenonas (Politologija, 1997)
The article deals with the citizenship policies of several post-communist countries (mainly the Baltic states and Ukraine), especially in the context of their search for national identity and the approach undertaken in the constitutions and relevant laws of these countries in regard to the issues of citizenship. Thus after examining the relevant provisions of the constitutions and laws concerning the definition of the initial body of citizens, acquisition, loss of citizenship, conditions for obtaining citizenship, the author debates the approach towards dual or multiple nationality. In this regard, the differences between the three Baltic states are pointed out. Legislation and ethnic policy of the Republic of Lithuania was not an obstacle for the integration into the international community and did not provoke any ethnic tension. Lithuania has defined the initial body of citizens in rather inclusive terms: the author argues that it was primarily based on the fact of residency on the territory of Lithuania at the moment of entry into force of the law on nationality. Estonia and Latvia started to shape their citizenship policy, unlike Lithuania, only after achieving independence. This was explained mainly by political reasons and much more cautious policies with respect to the granting of political rights to ethnic Russians and some other people of non-Estonian and non-Latvian origin. These policies were closely connected with the question of political sovereignty, as well as with restoration of the national identity. Nevertheless, such exclusiveness is ought to not become considered as a rough deviation from the usual practices. In similar cases, provided the lengthy period of foreign suppression which often had been aimed at weakening or even de-identifying the identity of those occupied, as well as isolating them from the process of international co-operation, similar limitations were usually taking place.The Baltic states, due to their illegal occupation in 1940, did not consider themselves as the successor states of the USSR and made some legal steps (which signified their position) in re-establishing the authority of several constitutional acts of the pre-war period. It seems more plausible that the Baltic states in their attempts to base the part of national legislation in conformity to the legislation which had existed until 1940, aimed rather at underlining their legal continuity than on restoring themselves ad integrum. Another point is that in part as a consequence of these policies quite a large number of permanent residents of Estonia and Latvia became stateless or acquired Russian citizenship. The need to eliminate the possibility of internal tensions requires further elaboration of the relevant legislation and, consequent, its implementation. One of the reasonable solutions could be the protection of rights of foreigners and to safeguard the constitutional rights which enshrine quite sufficient guarantees for non-citizens. The protection of rights of people not belonging to the majority in the Baltic states, first of all those who already acquired their respective citizenship, is also guaranteed by the laws on national minorities. A number of these people, because of the ongoing process of naturalization, is increasing. Besides, in Latvia (differently from Estonia and Lithuania) the protection of minorities is not related with citizenship.Russia is an exclusion between East European countries concerning approach towards dual citizenship. In this regard, bilateral treaties were propagated. Ukraine absolutely rejected the clause on dual citizenship proposed for inclusion in the Ukrainian-Russian Friendship and Co-operation treaty. The clause was widely perceived by the Ukrainian Government as a threat to independence and a step on the road to re-integration with Russia. Ukrainian legislation excludes dual citizenship, unless it is permitted by bilateral agreements. The citizenship issue was one of the contentious issues which impeded the final settlement of the status of the Crimean autonomy within Ukraine. The tendencies of the Crimean separatism manifested themselves insisting on the involvement of clauses on internal Crimean citizenship and the right of the Crimean citizens to dual citizenship into the constitution of the autonomy.One of the major differences between the Tatar Community in Crimea and Crimean and Ukrainian authorities remains the issue of Ukrainian citizenship for returning Tatar deportees. A significant number of returnees still are not Ukrainian citizens and that creates certain disabilities for these people. The case of the formerly deported peoples in Ukraine raises a number of legal questions. The same holds for the whole CIS region since, during the Stalin period, forcible population transfer was widely used and entire nationalities were deported. However, the absence of sufficient international mechanism to address all the issues concerned and the problems of its enforcement do not allow speeding up the settlement of all relevant problems.
Keywords: -